An interactive, self-guided tutorial on scientific writing for first year physiology students - Alex Swainson; Matthew J. Mason; Frances M. MacMillan (Current Research in Physiology)
Most biomedical science students arriving at UK universities have very limited experience of writing scientifically and have little insight into the process involved in producing a peer-reviewed academic publication. To help support them, we created an interactive, online tutorial to help improve their scientific writing through looking at aspects including the construction of a logical argument, use of figures and referencing, as well as providing an overview of the publication process. The tutorial was delivered in an in-person teaching workshop at the University of Bristol and offered as an optional, online-only activity at the University of Cambridge, in both cases to first-year physiology students. In Bristol, 68 % of 152 students and in Cambridge, 67 % of 561 students engaged with the interactive tutorial. These students were invited to complete before-and-after surveys, with questions relating to their confidence in and understanding of the topics covered. Feedback from students in both institutions was overwhelmingly positive, with a statistically significant increase in reported confidence and understanding following completion of the tutorial. We propose the use of similar interactive tutorials as a simple, low-investment way in which training in scientific writing can be included in undergraduate science curricula, to help students prepare for what is expected in coursework, exam essays and in their postgraduate careers.